Cultivating Critical Thinking in Literature Classroom Through Poetry - Azizi, Mahmoud; Azizi, Neshat; Lewandowska, Elwira; Gosteva, Yulia Nickolaevna; Majda, Peter (Journal of Education Culture and Society, 2022)
Aim. The development of learners’ CT is considered to be one of the most important skills in today’s fast pacing world. It has also been regarded as the mainstay of and an important component of literature teaching. However, this is one of those areas that was overlooked mainly in eastern culture in general and in the EFL classrooms in particular. Methods. To this end, to foster learners’ critical thinking skills, a poetry program was specifically designed to draw learners’ attention towards the significance of CT. Through a case study approach, a poetry program with a focus on culture-specific information was incorporated into the course. Four female students were engaged in a number of tasks in which they gradually learned to think critically through reflecting on and evaluating the assigned poems. A checklist was generated and used to observe and rate students’ CT before and after the intervention through teacher diaries. Results and conclusion. Analysis of the case study data indicated that students’ CT had improved and they developed good critical habits as a result of their involvement in the intervention. Thus, it was concluded that poetry could be regarded as a useful and effective source for developing critical thinking skills among students.